Method for producing polyvinyl alcohol film
By increasing the nitrogen-containing nonionic surfactant content in the film-forming stock solution for PVA films and adjusting it over time, the issue of streak-like defect deterioration is addressed, leading to reduced production losses and improved film quality.
Patent Information
- Application Number
- JP2022508283
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-17
- Filing Date
- 2021-03-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-03-11
AI Technical Summary
PVA films exhibit a gradual deterioration of streak-like defects over time, leading to increased production losses despite initial improvements with surfactant combinations and film formation techniques.
Increasing the amount of nitrogen-containing nonionic surfactant in the film-forming stock solution during PVA film production, specifically within the range of 0.10 to 0.30 parts by mass per 100 parts by mass of PVA, and adjusting this content over time to prevent defect deterioration.
This approach effectively suppresses the deterioration of streak-like defects over time, reducing production losses and maintaining film quality during continuous production.
Smart Images

Figure 0007653413000001
Abstract
Description
[Technical field]
[0001] The present invention relates to the production of polyvinyl alcohol films (hereinafter, "polyvinyl alcohol" may be abbreviated as "PVA"), and in particular to a technique for suppressing the increase in streak-like defects that occurs over operating time. [Background technology]
[0002] PVA film is used in a variety of applications, taking advantage of its unique properties regarding transparency, optical properties, mechanical strength, water solubility, etc. In particular, taking advantage of its excellent optical properties, PVA film is used as the raw material (raw film) of polarizing film that constitutes the polarizing plate, a basic component of liquid crystal displays (LCD), and its applications are expanding. LCD polarizing plates require high optical performance, and so does the polarizing film that is a component of them.
[0003] Many techniques related to PVA films and their manufacturing methods have been known so far. Patent Document 1 describes that a polyvinyl alcohol film containing a polyvinyl alcohol resin and three types of active agents, namely, a sulfate ester salt type anionic surfactant (a), an ether type nonionic surfactant (b), and a nitrogen-containing type nonionic surfactant (c), generates less optical streaks and has improved optical color unevenness and blocking properties than a film not containing any of the surfactants (a) to (c).
[0004] Patent Document 2 describes that the content of the surfactant in the film-forming solution containing PVA resin and water is preferably 0.01 to 0.5 parts by mass, more preferably 0.02 to 0.3 parts by mass, and even more preferably 0.05 to 0.1 parts by mass, per 100 parts by mass of polyvinyl alcohol, and the types and preferred contents of surfactants that improve the quality of PVA films are already known. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-206809 A [Patent Document 2] JP 2018-004707 A Summary of the Invention [Problem to be solved by the invention]
[0006] It was found that even when a film is produced using an extrusion film-producing apparatus with a combination of surfactant types and a preferred content range described in Prior Art Documents 1 and 2, for example, with a nitrogen-containing nonionic surfactant in an amount of 0.10 to 0.20 parts by mass per 100 parts by mass of PVA, the streaky defects on the film surface may gradually worsen over time. The problem to be solved by the present invention is to suppress the streaky defects on the film surface that worsen over time.
[0007] As a result of extensive research into achieving the above-mentioned object, the inventors discovered that the above-mentioned object can be achieved by increasing the amount of nitrogen-containing nonionic surfactant relative to PVA in the film-forming solution during film production, and thus arrived at the present invention. [Means for solving the problem]
[0008] That is, the present invention [1] A method for producing a polyvinyl alcohol film, comprising a step of discharging a film-forming solution containing 0.10 to 0.30 parts by mass of a nitrogen-containing nonionic surfactant per 100 parts by mass of polyvinyl alcohol from an extrusion film-forming apparatus, wherein in the discharging step, the content of the nitrogen-containing nonionic surfactant relative to the polyvinyl alcohol in the film-forming solution before being discharged is increased over time; [2] The content of the nitrogen-containing nonionic surfactant was adjusted by the extrusion of the film-forming solution at a discharge rate of 10 m 3the method for producing a polyvinyl alcohol film according to the above [1], wherein the amount of the polyvinyl alcohol is increased by 0.0005 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the polyvinyl alcohol; [3] The discharge amount of the film-forming solution from the extrusion film-forming device is 1 to 60 m 3 The method for producing a polyvinyl alcohol film according to [1] or [2], wherein the content of the nitrogen-containing nonionic surfactant is increased each time the [4] The method for producing a polyvinyl alcohol film according to any one of [1] to [3] above, wherein the film-forming solution further contains a plasticizer, and the content of the plasticizer in the film-forming solution is 1 to 20 parts by mass per 100 parts by mass of the polyvinyl alcohol. [5] The method for producing a polyvinyl alcohol film according to any one of [1] to [4] above, wherein the film has a thickness of 10 to 80 μm. [6] The method for producing a polyvinyl alcohol film according to any one of [1] to [5] above, wherein the film width is 3 m or more. Regarding. Effect of the Invention
[0009] According to the present invention, it is possible to suppress the deterioration of streak-like defects over time during continuous production of PVA films, thereby bringing about the effect of reducing production losses. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The film-forming solution used in the method for producing the PVA film of the present invention contains PVA. As the PVA, one produced by saponifying a vinyl ester-based polymer obtained by polymerizing a vinyl ester can be used. Examples of the vinyl ester include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate. These may be used alone or in combination of two or more, but the former is preferred. From the viewpoints of availability, cost, productivity, and the like, vinyl acetate is preferred as the vinyl ester.
[0011] During the polymerization of the vinyl ester, other monomers copolymerizable with the vinyl ester may be copolymerized.Examples of such other monomers include ethylene; olefins having 3 to 30 carbon atoms, such as propylene, 1-butene, and isobutene; acrylic acid or a salt thereof; acrylic acid esters, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid or a salt thereof; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, methacrylic acid, and the like. Methacrylic acid esters such as i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamides such as acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, acrylamidopropanesulfonic acid or a salt thereof, acrylamidopropyldimethylamine or a salt thereof, and N-methylolacrylamide or a derivative thereof; methacrylamide derivatives such as methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidepropanesulfonic acid or a salt thereof, methacrylamidepropyldimethylamine or a salt thereof, N-methylolmethacrylamide or a derivative thereof; N-vinylamides such as N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or a salt, ester, or acid anhydride thereof; itaconic acid or a salt, ester, or acid anhydride thereof; vinyl silyl compounds such as vinyltrimethoxysilane; and isopropenyl acetate.These other monomers may be used alone or in combination of two or more. Among them, as the other monomers, ethylene and olefins having 3 to 30 carbon atoms are preferred, and ethylene is more preferred.
[0012] The proportion of the structural units derived from the other monomers in the vinyl ester polymer is not particularly limited, but is preferably 15 mol % or less, and more preferably 5 mol % or less, based on the number of moles of all structural units constituting the vinyl ester polymer.
[0013] Although there is no particular restriction on the degree of polymerization of PVA, since the film strength tends to decrease as the degree of polymerization decreases, it is preferably 200 or more, more preferably 300 or more, even more preferably 400 or more, and particularly preferably 500 or more. Furthermore, since the viscosity of the aqueous solution or molten PVA increases when the degree of polymerization is too high, and film formation tends to become difficult, it is preferably 10,000 or less, more preferably 9,000 or less, even more preferably 8,000 or less, and particularly preferably 7,000 or less. Here, the degree of polymerization of PVA means the average degree of polymerization measured in accordance with the description of JIS K6726-1994, and is calculated by the following formula from the intrinsic viscosity [η] (unit: deciliter / g) measured in water at 30°C after resaponification and purification of PVA. Degree of polymerization = ([η]×10 4 / 8.29) (1 / 0.62)
[0014] There is no particular limitation on the saponification degree of PVA, and for example, PVA of 60 mol% or more can be used, but when the PVA film is used as a raw film for manufacturing optical films such as polarizing films, the saponification degree of PVA is preferably 95 mol% or more, more preferably 98 mol% or more, and even more preferably 99 mol% or more. Here, the saponification degree of PVA means the ratio (mol%) of the number of moles of the vinyl alcohol unit to the total number of moles of the structural unit (typically a vinyl ester monomer unit) that can be converted into a vinyl alcohol unit by saponification that PVA has and the vinyl alcohol unit. The saponification degree of PVA can be measured according to the description of JIS K6726-1994.
[0015] The PVA may be one type of PVA used alone, or two or more types of PVA with different polymerization degrees, saponification degrees, modification degrees, etc. may be used in combination. However, if the PVA film contains PVA with functional groups that promote crosslinking reactions, such as PVA with acidic functional groups such as carboxyl groups and sulfonic acid groups; PVA with acid anhydride groups; PVA with basic functional groups such as amino groups; and neutralized products thereof, the secondary processability of the PVA film may be reduced due to crosslinking reactions between PVA molecules. Therefore, in cases where excellent secondary processability is required, such as raw films for optical film production, the contents of PVA with acidic functional groups, PVA with acid anhydride groups, PVA with basic functional groups, and neutralized products thereof in the PVA are preferably 0.1 mass% or less, and more preferably none of them are contained.
[0016] In the present invention, the content of PVA in the film-forming solution is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less, and preferably 10% by mass or more, and more preferably 20% by mass or more.
[0017] The nitrogen-containing nonionic surfactants used in the present invention include fatty acid diethanolamides and fatty acid alkanolamides.
[0018] In the present invention, the film-forming solution must contain 0.10 to 0.30 parts by mass of a nitrogen-containing nonionic surfactant per 100 parts by mass of polyvinyl alcohol, more preferably 0.10 to 0.20 parts by mass, and even more preferably 0.12 to 0.18 parts by mass, per 100 parts by mass of polyvinyl alcohol.
[0019] In the present invention, in the process of discharging the film-forming solution from the extrusion film-forming apparatus, it is necessary to increase the content of the nitrogen-containing nonionic surfactant over time relative to the content of polyvinyl alcohol in the film-forming solution before it is discharged. By doing so, it is possible to suppress the deterioration of streaky defects over time when PVA films are continuously produced. This is presumably because the unevenness of dirt adhering to the flow path surface inside the extrusion film-forming apparatus can be alleviated by continuous operation.
[0020] In the present invention, the extrusion film forming device discharges a film forming solution of 10 m 3 It is preferable to increase the content of the nitrogen-containing nonionic surfactant in the range of 0.0005 parts by mass to 0.1 parts by mass to 100 parts by mass of polyvinyl alcohol. By setting it in this range, the effect of the present invention can be obtained more significantly, and even if film formation is continued for a long time, problems due to the surfactant content being too high are unlikely to occur. It is more preferable to increase the content of the nitrogen-containing nonionic surfactant in the range of 0.001 parts by mass to 0.05 parts by mass, and even more preferable to increase it in the range of 0.002 parts by mass to 0.02 parts by mass.
[0021] In the present invention, the method for increasing the content of the nitrogen-containing nonionic surfactant in the polyvinyl alcohol over time is not particularly limited. 3The content of the nitrogen-containing nonionic surfactant is preferably increased every time the discharge amount of the film-forming raw solution from the extrusion film-forming apparatus reaches 3 to 50 m. 3 It is preferable that the distance is every 5 to 40 m. 3 It is more preferable that the content of the nitrogen-containing nonionic surfactant is increased stepwise or continuously. In this case, the content of the nitrogen-containing nonionic surfactant may be increased stepwise or continuously. The stepwise increase method is preferable in that the manufacturing conditions can be easily controlled. The continuous increase method is preferable in that the quality of the product is less likely to become unstable before and after the change in the content of the surfactant compared to the stepwise increase method.
[0022] In the present invention, a surfactant other than the nitrogen-containing nonionic surfactant, for example, a nonionic surfactant not containing nitrogen, or an anionic surfactant may be further used. Examples of these include fatty acid polyethylene glycol and glycerin fatty acid ester. The content of the surfactant other than the nitrogen-containing nonionic surfactant is preferably 0.1 to 0.3 parts by mass relative to 100 parts by mass of polyvinyl alcohol, and more preferably 0.12 to 0.2 parts by mass relative to 100 parts by mass of polyvinyl alcohol.
[0023] From the viewpoint of imparting flexibility to the PVA film, it is preferable that the film-forming solution further contains a plasticizer. Preferred plasticizers include polyhydric alcohols, specifically ethylene glycol, glycerin, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, etc. These may be used alone or in combination of two or more. Among them, ethylene glycol or glycerin is preferable from the viewpoint of compatibility with PVA and availability.
[0024] The content of the plasticizer in the film-forming solution is preferably within the range of 1 to 20 parts by mass with respect to 100 parts by mass of polyvinyl alcohol.
[0025] The film-forming solution may further contain non-volatile components other than polyvinyl alcohol, nitrogen-containing nonionic surfactants, other surfactants, and plasticizers, as necessary. Examples of such non-volatile components include antioxidants, ultraviolet absorbers, lubricants, colorants, fillers (inorganic particles, starch, etc.), preservatives, antifungal agents, and polymer compounds other than the above-mentioned components. The content of other non-volatile components in the film-forming solution is preferably 10% by mass or less.
[0026] The thickness of the PVA film obtained by the manufacturing method of the present invention is not particularly limited, and can be appropriately set depending on the use of the PVA film, for example, 300 μm or less. When the PVA film is used as a raw film for manufacturing an optical film such as a polarizing film, the thickness is preferably within the range of 10 to 80 μm. The thickness of the PVA film can be calculated as the average value of values measured at any 10 points.
[0027] The shape of the PVA film obtained by the manufacturing method of the present invention is not particularly limited, but it is preferably a long film because it allows for smooth continuous production of a more uniform PVA film and because it is used continuously when manufacturing an optical film, etc. The length of the long film (length in the machine direction) is not particularly limited and can be appropriately set depending on the application, and can be within the range of, for example, 5 to 30,000 m. It is preferable to make the long film into a film roll by winding it around a core.
[0028] The width of the PVA film obtained by the manufacturing method of the present invention is not particularly limited, and can be, for example, 0.5 m or more. In recent years, a wide polarizing film has been required, so the width is preferably 1 m or more, more preferably 3 m or more, even more preferably 4.5 m or more, particularly preferably 5.0 m or more, and most preferably 5.5 m or more. On the other hand, if the width of the PVA film is too wide, the manufacturing cost of the film-forming device for forming the PVA film increases, and further, when an optical film is manufactured using a manufacturing device that is in practical use, it becomes difficult to uniformly stretch the PVA film, so the width of the PVA film is preferably 7.5 m or less, more preferably 7.0 m or less, and even more preferably 6.5 m or less.
[0029] According to the present invention, when a polyvinyl alcohol film is produced using an extrusion film-producing apparatus, it is possible to suppress the tendency for streak-like defects on the film surface to gradually increase over time.
[0030] Examples of the liquid medium in the film-forming solution include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerin, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, diethylenetriamine, etc., and one or more of these can be used. Among these, water is preferred from the viewpoints of its small environmental impact and ease of recovery.
[0031] The volatile fraction of the film-forming solution (the content in the film-forming solution of volatile components such as the liquid medium that are removed by volatilization or evaporation during film formation) varies depending on the film-forming method, film-forming conditions, etc., but is preferably in the range of 40 to 90 mass%, and more preferably in the range of 45 to 80 mass%. When the volatile fraction of the film-forming solution is 40 mass% or more, the viscosity of the film-forming solution does not become too high, making film formation easy. On the other hand, when the volatile fraction of the film-forming solution is 90 mass% or less, the viscosity of the film-forming solution does not become too low, improving the thickness uniformity of the obtained PVA film.
[0032] A specific method for producing a PVA film using the above film-forming solution is, for example, an extrusion film-forming method in which the film-forming solution that has been heated and melted is discharged onto a support such as a metal drum or a metal belt using an extrusion film-forming device, and then dried on the support. The obtained film may be further dried using a drying roll or a hot air drying device, heat-treated using a heat treatment device, or humidity-controlled using a humidity control device, if necessary. The produced PVA film is preferably wound around a core to form a film roll. In addition, both ends of the produced PVA film in the width direction may be cut off.
[0033] The PVA film obtained by the manufacturing method of the present invention can be suitably used as a raw film for manufacturing optical films such as polarizing films, retardation films, and special light-collecting films. By using the PVA film obtained by the manufacturing method of the present invention, it is possible to obtain an optical film with few streak-like defects and high quality. The PVA film obtained by the manufacturing method of the present invention can also be used as a packaging material, a water-soluble film for laundry bags, etc., a release film for manufacturing artificial marble, etc. In particular, the PVA film obtained by the manufacturing method of the present invention is suitably used as a raw film for manufacturing polarizing films.
[0034] A preferred embodiment of the present invention is a method for producing a polarizing film comprising a step of dyeing the PVA film and a step of stretching the film. The production method may further comprise a fixing step, a drying step, a heat treatment step, or the like. The order of dyeing and stretching is not particularly limited, and the dyeing step may be performed before the stretching step, simultaneously with the stretching step, or after the stretching step. The steps of stretching, dyeing, etc. may be repeated multiple times. In particular, it is preferable to divide the stretching step into two or more stages, since this makes it easier to perform uniform stretching.
[0035] Dyes used for dyeing the PVA film include iodine or dichroic organic dyes (e.g., dichroic dyes such as DirectBlack 17, 19, 154; DirectBrown 44, 106, 195, 210, 223; DirectRed 2, 23, 28, 31, 37, 39, 79, 81, 240, 242, 247; DirectBlue 1, 15, 22, 78, 90, 98, 151, 168, 202, 236, 249, 270; DirectViolet 9, 12, 51, 98; DirectGreen 1, 85; DirectYellow 8, 12, 44, 86, 87; DirectOrange 26, 39, 106, 107, etc.). These dyes can be used alone or in combination of two or more. Dyeing can usually be carried out by immersing the PVA film in a solution containing the above dye, but the treatment conditions and method are not particularly limited.
[0036] Methods for stretching a PVA film include uniaxial stretching and biaxial stretching, with the former being preferred. The uniaxial stretching of a PVA film in the machine direction (MD) or the like may be performed by either wet stretching or dry heat stretching, but wet stretching is preferred from the viewpoint of the performance and quality stability of the resulting polarizing film. Examples of wet stretching include a method in which a PVA film is stretched in pure water, an aqueous solution containing various components such as additives and water-soluble organic solvents, or an aqueous dispersion in which various components are dispersed. Specific examples of the uniaxial stretching method using the wet stretching method include a method of uniaxially stretching in warm water containing boric acid, a method of uniaxially stretching in a solution containing the dye, or a method of uniaxially stretching in a fixing treatment bath described below. In addition, the PVA film after absorbing water may be uniaxially stretched in air, or may be uniaxially stretched by other methods.
[0037] The stretching temperature during uniaxial stretching is not particularly limited, but in the case of wet stretching, a temperature within the range of preferably 20 to 90°C, more preferably 25 to 70°C, and even more preferably 30 to 65°C is adopted, and in the case of hot stretching, a temperature within the range of preferably 50 to 180°C is adopted.
[0038] The stretching ratio in the uniaxial stretching process (total stretching ratio when uniaxial stretching is performed in multiple stages) is preferably as high as possible to immediately before the film breaks in terms of polarization performance, and specifically, is preferably 4 times or more, more preferably 5 times or more, and even more preferably 5.5 times or more. There is no particular upper limit to the stretching ratio as long as the film does not break, but in order to perform uniform stretching, it is preferably 8.0 times or less.
[0039] In the production of polarizing films, it is preferable to carry out a fixing treatment in order to strengthen the adsorption of the dye to the uniaxially stretched PVA film. As the fixing treatment, a method of immersing the PVA film in a treatment bath containing a general boric acid and / or a boron compound can be adopted. In this case, an iodine compound may be added to the treatment bath as necessary.
[0040] It is preferable that the PVA film that has been subjected to the uniaxial stretching treatment or the uniaxial stretching treatment and the fixing treatment is then subjected to a drying treatment or a heat treatment. The temperature for the drying treatment or the heat treatment is preferably 30 to 150°C, and particularly preferably 50 to 140°C. If the temperature is too low, the dimensional stability of the obtained polarizing film is likely to decrease. On the other hand, if the temperature is too high, the polarization performance is likely to decrease due to the decomposition of the dye, etc.
[0041] A polarizing plate can be produced by laminating an optically transparent and mechanically strong protective film on either or both sides of the polarizing film obtained as described above. In this case, the protective film may be a cellulose triacetate (TAC) film, a cellulose acetate butyrate (CAB) film, an acrylic film, or a polyester film. In addition, PVA adhesives and urethane adhesives are generally used as adhesives for laminating the protective film, and among these, PVA adhesives are preferably used.
[0042] The polarizing plate obtained as described above can be used as a part of a liquid crystal display device by coating it with an acrylic adhesive or the like and then bonding it to a glass substrate. When bonding the polarizing plate to the glass substrate, a retardation film, a viewing angle improving film, a brightness improving film, etc. may be bonded at the same time.
[0043] (Example) The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0044] (Method of evaluating streak-like defects) A streak-like defect is a defect observed as a continuous line in the machine flow direction (MD direction) during film production, and when light transmitted through the film surface is projected onto a white wall or the like using a light source, a continuous light or dark pattern in the MD direction can be confirmed. A film with a streak-like defect has a difference in height between the concave or convex parts on the surface, and can be visually confirmed as the light or dark pattern. Specifically, a sample piece cut out from the PVA film obtained in the following Examples, Comparative Examples, or Reference Examples with a length of 1.5 m in the MD direction and full width was hung so that the MD direction was up and down, and a halogen lamp light source manufactured by S-1 Co., Ltd. with a luminous intensity of about 550 Lux was installed at a position 350 cm away from the film surface, and light was projected perpendicularly onto the film surface. Next, the light transmitted through the film was projected onto a white wall 10 cm away from the film, and the light or dark pattern in the form of a streak-like pattern visually confirmed was judged to be a streak-like defect. The height difference of the film thickness was measured for each part of the film corresponding to the visually confirmed streak-like defects using a contact thickness meter "KG601A" manufactured by Anritsu Corporation. As the evaluation criteria, streak-like defects with a height difference of less than 0.10 μm were assigned 1 point per piece, those with a height difference of 0.10 μm or more and less than 0.15 μm were assigned 5 points per piece, and those with a height difference of 0.15 μm or more were assigned 10 points per piece, and the total score of all streak-like defects occurring in the sample piece was used as the film surface score. In this evaluation method, the worse the streak-like defects are, the higher the film surface score is. Films with no streak-like defects and those with a film surface score of 0 points and 1 to 5 points were considered to be pass, and those with a film surface score of 6 points or more were considered to be fail.
[0045] Manufacturing Example As the PVA, chips of PVA (saponified homopolymer of vinyl acetate) with a degree of polymerization of 2400 and a degree of saponification of 99.9 mol% were used. 100 parts by mass of the PVA chips were immersed in water at 50 ° C for 1 hour, and then centrifuged to obtain PVA water-containing chips. The volatile content in the obtained PVA water-containing chips was 50% by mass. 200 parts by mass of the PVA water-containing chips (100 parts by mass of PVA in a dry state) were mixed with 12 parts by mass of glycerin, 0.12 parts by mass of a nitrogen-containing nonionic surfactant (fatty acid diethanolamide), 0.08 parts by mass of an anionic surfactant, and 130 parts by mass of water (the total amount of water after mixing was 230 parts by mass relative to 100 parts by mass of PVA), and the resulting mixture was heated and melted (maximum temperature 130 ° C) in a single-screw extrusion film-forming machine to obtain a film-forming stock solution. This film-forming solution was cooled to 100°C in a heat exchanger, and then discharged from a 390 cm wide coat hanger die onto a drum with a surface temperature of 90°C to form an extrusion film. The film was then dried using a hot air dryer, and both ends of the film, which had become thick due to neck-in during film formation, were cut off to continuously produce a PVA film with a thickness of 60 μm and a width of 300 cm.
[0046] Reference example 1 In the above manufacturing example, the discharge volume from the start of manufacturing was 0.6 m 3 When the film had reached this state (3 hours after the start of production), the PVA film was evaluated for streaks by the method described above. The results are shown in Table 1.
[0047] Comparative Example 1 Continuing from Reference Example 1, the content of the nitrogen-containing nonionic surfactant in the film-forming solution was kept constant at 0.12 parts by mass per 100 parts by mass of PVA, and film production was continued. The discharge amount of the film-forming solution from the start of film production was 28 m 3 The PVA film obtained when the temperature reached 135 hours after the start of production was evaluated for streaks by the above-mentioned method. The results are shown in Table 1.
[0048] Example 1 The film production was continued from Comparative Example 1, and the discharge amount of the film-forming solution from the start of film production was 29 m 3When the film was formed (140 hours after the start of production), the content of the nitrogen-containing nonionic surfactant in the film-forming solution was changed from 0.12 parts by mass to 0.14 parts by mass per 100 parts by mass of PVA, and the PVA film obtained after film formation for another 2 hours was evaluated for streaks by the above-mentioned method. The results are shown in Table 1.
[0049] Reference example 2 Continuing from Example 1, the content of the nitrogen-containing nonionic surfactant in the film-forming solution was kept constant at 0.14 parts by mass per 100 parts by mass of PVA, and film production was continued. The discharge amount of the film-forming solution from the start of film production was 45 m 3 The PVA film obtained when the temperature reached 100° C. (217 hours after the start of production) was evaluated for streaks by the method described above. The results are shown in Table 1.
[0050] Example 2 The film production was continued from the above-mentioned Reference Example 2, and the discharge amount of the film-forming raw material solution from the start of film production was 58 m 3 When the film formation temperature reached 100°C (280 hours after the start of production), the content of the nitrogen-containing nonionic surfactant in the film-forming solution was changed from 0.14 parts by mass to 0.16 parts by mass per 100 parts by mass of PVA, and the PVA film obtained after film formation for another 2 hours was evaluated for streaks by the above-mentioned method. The results are shown in Table 1.
[0051] Comparative Example 2 A PVA film was produced in the same manner as in the above-mentioned Production Example, except that the content of the nitrogen-containing nonionic surfactant in the film-forming solution was changed to 0.05 parts by mass per 100 parts by mass of PVA. The discharge amount of the film-forming solution was 0.6 m. 3 When the film had reached this state (3 hours after the start of production), the PVA film was evaluated for streaks by the method described above. The results are shown in Table 1.
[0052] Comparative Example 3 The film production was continued from Comparative Example 2, and the discharge amount of the film-forming raw material solution from the start of film production was 30 m 3The PVA film obtained when the temperature reached 145 hours after the start of production was evaluated for streaks by the above-mentioned method. The results are shown in Table 1.
[0053] Comparative Example 4 A PVA film was produced in the same manner as in the above-mentioned production example, except that the content of the nitrogen-containing nonionic surfactant in the film-producing solution was changed to 0.35 parts by mass per 100 parts by mass of PVA. 3 When the film had reached this state (3 hours after the start of production), the PVA film was evaluated for streaks by the method described above. The results are shown in Table 1.
[0054] Comparative Example 5 The film production was continued from Comparative Example 4, and the discharge amount from the start of production was 25 m 3 The PVA film obtained when the temperature reached 120 hours after the start of production was evaluated for streaks by the above-mentioned method. The results are shown in Table 1.
[0055] [Table 1]
[0056] Comparing Comparative Example 1 and Example 1, the discharge capacity of the extrusion film forming device was 28 m 3 , 29m 3 The film surface scores when the amounts of the nitrogen-containing nonionic surfactants were 0.12 parts by mass to 0.14 parts by mass relative to 100 parts by mass of PVA as in Example 1 were 8 points and 5 points, respectively, and the film surface scores were lower, and the tendency for the streaky defects to worsen was improved. Furthermore, when comparing Reference Example 2 and Example 2, the film surface scores were 31 points and 3 points, respectively, and similarly, the tendency for the streaky defects to worsen was improved by increasing the amount of the nitrogen-containing nonionic surfactant. On the other hand, as shown in Comparative Examples 2 and 3, when the amount of nitrogen-containing nonionic surfactant was constant and too small at 0.05 parts by mass per 100 parts by mass of PVA, many streaky defects were observed from the start of operation, and the condition worsened as operation continued. Furthermore, as shown in Comparative Examples 4 and 5, when the amount of nitrogen-containing nonionic surfactant was constant and excessively large at 0.35 parts by mass relative to 100 parts by mass of PVA, many streak-like defects were observed from the start of operation, and the condition worsened as operation continued. In addition, as shown in Reference Example 1, when the amount of the nitrogen-containing nonionic surfactant is 0.12 parts by mass relative to 100 parts by mass of PVA, the film was formed 3 hours after the start of film production (when the discharge amount of the film-forming raw solution from the start of film production was 0.6 m 3 However, as shown in Comparative Example 1, when the film production was continued under the same conditions as in Reference Example 1, the film surface score was 0 and no streak-like defects occurred. 3 At this point, the film surface had 8 points and many streak-like defects.
[0057] As described above, by increasing the amount of nitrogen-containing nonionic surfactant relative to PVA over time as in the present invention, it is possible to continuously produce PVA films in which the occurrence of streak-like defects is suppressed.
Claims
1. A method for producing a polyvinyl alcohol film, comprising a step of discharging a film-forming stock solution containing 0.10 to 0.30 parts by mass of a nitrogen-containing nonionic surfactant per 100 parts by mass of polyvinyl alcohol from an extrusion film-forming device, wherein in the discharging step, the content of the nitrogen-containing nonionic surfactant relative to the polyvinyl alcohol in the film-forming stock solution before being discharged is increased over time.
2. The content of the nitrogen-containing nonionic surfactant was adjusted by the extrusion film-forming device at a discharge rate of 10 m 3 The method for producing a polyvinyl alcohol film according to claim 1 , wherein the amount of the polyvinyl alcohol is increased in a range of 0.0005 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the polyvinyl alcohol.
3. The extrusion film forming device discharges the film forming solution at a rate of 1 to 60 m 3 The method for producing a polyvinyl alcohol film according to claim 1 or 2, wherein the content of the nitrogen-containing nonionic surfactant is increased every time the polyvinyl alcohol film reaches a temperature of 100° C. or more.
4. The method for producing a polyvinyl alcohol film according to any one of claims 1 to 3, wherein the film-forming solution further contains a plasticizer, and the content of the plasticizer in the film-forming solution is 1 to 20 parts by mass per 100 parts by mass of the polyvinyl alcohol.
5. The method for producing a polyvinyl alcohol film according to any one of claims 1 to 4, wherein the thickness of the film is 10 to 80 µm.
6. The method for producing a polyvinyl alcohol film according to any one of claims 1 to 5, wherein the film width is 3 m or more.
Citation Information
Patent Citations
Polyvinyl alcohol-based film and use of the same
JP2005206809A
Polyvinyl alcohol film and method for producing the same
JP2006188661A
Method for producing polyvinyl alcohol film
JP2016222834A
Method for producing polyvinyl alcohol-based film, polyvinyl alcohol-based film, and polarizing film
JP2017213878A
Manufacturing method for optical films
JP2018004707A